Application Value of Different Detection Methods in Diagnosis and Prognosis of Multiple Myeloma - Zhou, Ziyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Multiple myeloma (MM), being a hematological tumor with a high incidence, has seriously threatened people's health and drawn the attention of numerous research. In recent years, along with the continuous advancement of research, an increasing number of technologies have been utilized in the diagnosis and prognosis evaluation of MM, and the approaches for the diagnosis and prognosis assessment of MM have become increasingly diversified. Cytogenetic detection, molecular biology detection, hematological detection and imaging detection are widely used in the diagnosis and prognosis evaluation of MM. In addition, researchers are also using immunological detection, detection of circulating tumor cells and DNA, machine learning and other methods to actively search for new biological targets, and try the combined application of multiple diagnostic pathways to continuously optimize the diagnosis and prognosis evaluation of MM. This paper reviewed several methods for the diagnosis and prognostic evaluation of MM, analyzed some advantages and disadvantages of each method in the diagnosis and prognostic evaluation, and put forward some thoughts for future research directions.